Pengaruh Kinerja Keuangan, Good Corporate Governance dan Kebijakan Hutang Terhadap Nilai Perusahaan pada Persusahaan Sektor Infrastruktur, Utilitas dan Transportasi yang Terdaftar di BEI - Rohmah El Yunussyah; Jeni Susyanti; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTThis study aims to conduct empirical testing on the effect of financial performance, good corporate governance and debt policy on company value in Infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange in the period 2016-2019. Based on the criteria used by researchers, a total of 56 samples were obtained. Analysis of the data used in this study is multiple linear regression analysis. In this study, financial performance is obtained by calculating ROA. For the measurement of good corporate governance is done by calculating the size of the board of commissioners, the independence of commissioners and the audit committee. For the debt policy in this study using DER.From the results of this study, it can be seen that ROA has a positive and significant effect on firm value, the size of the board of commissioners has a positive but not significant effect on company value, independent commissioners have a positive effect but not significant on company value, the audit committee has a positive but not significant effect on company value, while DER has a positive and significant effect on company value.Keywords: Company value, financial performance, good corporate governance, debt policy.